Philosophy, Dogma, and Exegesis in Medieval Ashkenazic Judaism: The Evidence of Sefer Hadrat Qodesh - Davis, Joseph M. (AJS review, 1993)
During the Middle Ages, each Mediterranean land, from one end of the sea to the other, had its Jewish philosophers. There was one region and one Jewish culture, however, that made no contribution at all to the writing of medieval Jewish philosophy. That was Ashkenazic or Northern European Judaism, the culture of the Jews of England, Northern France, Germany, and Eastern Europe north of the Balkans.